Relasi Agama dan Negara dalam Perspektif Ahmad Syafii Ma’arif dan Abdullahi Ahmed An-Na’im: Studi Komparatif tentang Demokrasi, Pluralisme, dan Konstitusionalisme Islam - Salman Al Farisi (Medan Resource Center, 2024)
The relationship between religion and the state remains a central issue in contemporary Islamic political thought, particularly in the context of modern nation-states characterized by religious and cultural diversity. Various Muslim intellectuals have proposed different perspectives regarding the ideal model of interaction between religious values and state governance. This study aims to analyze and compare the ideas of Ahmad Syafii Maarif and Abdullahi Ahmed An-Na’im concerning the relationship between religion and the state within the framework of Islamic political thought. The research employs a qualitative descriptive method based on library research, utilizing books, journal articles, and relevant academic publications as primary sources. The analysis is conducted through normative, conceptual, and historical approaches. The findings reveal that both scholars emphasize the importance of democratic values, justice, and respect for human rights in state administration. However, they differ in their emphasis and contextual interpretation of religion-state relations. Ahmad Syafii Maarif advocates the substantive integration of Islamic ethical values within a pluralistic state framework, whereas Abdullahi Ahmed An-Na’im argues for a secular state that guarantees religious freedom while allowing religion to function as a moral force in the public sphere. This study contributes to the development of contemporary Islamic political discourse by providing a comparative understanding of two influential Muslim thinkers and offering insights into the construction of an inclusive and democratic model of religion-state relations in modern Muslim societies